Promoting Social Inclusion through Sport for Refugee-Background Youth in Australia: Analysing Different Participation Models - Block, Karen (2017)
Sports participation can confer a range of physical and psychosocial benefits and, for refugee and migrant youth, may even act as a critical mediator for achieving positive settlement and engaging meaningfully in Australian society. This group has low participation rates however, with identified barriers including costs; discrimination and a lack of cultural sensitivity in sporting environments; lack of knowledge of mainstream sports services on the part of refugee-background settlers; inadequate access to transport; culturally determined gender norms; and family attitudes. Organisations in various sectors have devised programs and strategies for addressing these participation barriers. In many cases however, these responses appear to be ad hoc and under-theorised. This article reports findings from a qualitative exploratory study conducted in a range of settings to examine the benefits, challenges and shortcomings associated with different participation models. Interview participants were drawn from non-government organisations, local governments, schools, and sports clubs. Three distinct models of participation were identified, including short term programs for refugee-background children; ongoing programs for refugee-background children and youth; and integration into mainstream clubs. These models are discussed in terms of their relative challenges and benefits and their capacity to promote sustainable engagement and social inclusion for this population group.